Preparation and Characterization of Glass Ionomer Cements with Added Carboxymethyl Chitosan. Issue 6 (2nd June 2020) - Bao, Xiaozhen; Liu, Fang; He, Jingwei
Abstract: Because of their low fracture strength, glass ionomer cements (GICs) can not be applied to the high stress loading areas in dentistry. With the aim to improve the fracture properties of GICs, carboxymethyl chitosan (CMCS) was dissolved in the liquid part of a commercial GIC, Fuji IX, and then mixed with inorganic particles to prepare GICs containing CMCS. The mechanical performance of the GICs containing CMCS showed that the CMCS could enhance the fracture properties of GICs when its concentration in the GICs was in a certain range; 0.0125 wt.% of CMCS in the liquid part of GIC improved both the flexural strength and the fracture toughness. The flexural strength, flexural modulus, and compressive strength results of the GICs containing CMCS after water aging showed that they also had good water aging-resistance.